L-Glutamic acid release from a series of aluminum-based isoreticular porous coordination polymers1. Issue 20 (28th May 2015) - Nakahama, Masashi; Reboul, Julien; Yoshida, Kenji; Furukawa, Shuhei; Kitagawa, Susumu
<x xml:space="preserve">Abstract</x> The releasing property of l-glutamic acid from a series of aluminum MOFs was investigated in physiological condition.